Spectrophotometric Express Method in Bioindication of Park Ecosystems - Nebesny, V.B.; Grodzynska, G.A.; Samchuk, A.I.; Dugin, S.S.; Honchar, H.Yu. (Science and Innovation, 2024)
Introduction. Park areas perform conservational and recreational functions in an urban environment that is under the influence of intense manmade load. Problem Statement. The global decline in air quality, the augmentation of toxic emissions and industrial wastes, require constant monitoring of the environment, which must be focused primarily on biotic parameters. Purpose. estimation of the manmade pollution of park ecosystems of kyiv according to the spectral characteristics of leaves of the bioindicator species Taraxacum officinale F.h. Wigg., and the content of heavy metals in them and in the soils. Materials and Methods. Spectrophotometry method for studying the spectral characteristics of T. officinale leaves; induction-coupled plasma mass spectrometry (iCP-Ms) method for measuring the content of Cu, Pb, Zn, Mn, Ni, Cr in leaves and soils from localities; statistical methods. Results. The average level of correlations (0.50-0.69) between vegetation indices R550/R485, R550/R620, R450/R735, NDVI, RESV, SI and Cu content is shown, Pb, Mn in leaves and Pb and Mn — in soils, and a high degree of correlation (0.75-0.87) between the indices R450/R735, NDVI, RESV, LCI and the content of zn and Cr in leaves and soils. There is a clear trend of increasing the content of heavy metals in the direction from the central parts of the park areas to the peripheral ones, which are intensively affected by traffic. The most polluted is the Mariinsky Park. high levels of heavy metals Cu, Pb and Cr were also found in the soils and leaves of the park of the kyiv Polytechnic institute. The lowest level of pollution is in the Feofaniya park. Conclusions. The discussed vegetation indices are recommended both for rapid assessment of the state of natural and urban ecosystems, and for interpretation of satellite images for zoning and to determine the degree of man-made pollution. The use of the spectrophotometric method for bioindication is promising due to a high speed of obtaining results, a wide coverage, and a low cost.